Climate Change as a Narrative Device to Resolve the Plot. The TV series The Affair as a Case Study - Iapalucci, Greta (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
Contemporary TV series have become narratively complex in the realm, among others, of time management and genre hybridization. As part of this transformation, serialized narratives have increasingly accommodated social and cultural themes. One worldwide modern concern is the ecological emergency, which has led both to the emergence of a dedicated narrative genre known as cli-fi and to the insertion of climate change impacts in the background of the narrative of several audiovisual products, independently of their genre. One remarkable TV series in which the environmental crisis is encountered is the American TV drama The Affair (Showtime, 2014-2019), created by Sarah Treem and Hagai Levi and starring Dominic West and Ruth Wilson, playing respectively Noah Solloway and Alison Bailey. After having followed the marital and extramarital relationships of the two protagonists, the last season of the TV series, season 5, branches the storytelling by introducing a new timeline located in an unclear future after 2053 along with the well-established contemporary one. The bifurcation of the narration represents the quintessential expedient to introduce the topic of climate change into the TV series, paving its way in the former timeline and effectively displaying it in the following one. By means of a qualitative content analysis of the 11 episodes of season 5 of The Affair, the aim of this contribution is twofold: first, to identify and shed light on climate change phenomena and effects introduced in the product and, second, to investigate the purposes of their employment in the storytelling. Findings have shown, on the one hand, that the ecological crisis is represented by means of extreme weather phenomena, insufficient resources and extinction and, on the other hand, that it is used to resolve the main affective and sentimental storylines, becoming a narrative device to achieve the Gran Finale of the TV series and to collaterally raise awareness on the issue in a large audience. Future research is required to illustrate whether The Affair’s effectively succeeded in stimulating reflections on this global concern among the audience.